"(NkULXTURNA REWOL@C)QÆQ(B" (NW uKRAÇNÆ(B, (NABO uPRAWLÆNNQ DEGRADACÆÃ@ (B/s)E - (NsEN^ENKO(B, (Nm(B. )Qæ.,s)E ((NkI)QÇW (B:s)E (Nmaup(B,s, 2004)
(NkNIGA PRISWQ^ENA (B"(NKULXTURN)QÆJ REWOL@CÆÇ(B" (NW uKRAÇNÆ U (BXX - (NNA PO^ATKU (BXXI (NST(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NsOC)QÆOLOGÆQ KULXTURIs)E -- (NuKRA)QÇNAs)E; (NkULXTURNA REWOL@C)QÆQs)E -- (NuKRA)QÇNAs)E; (NUPRAWL)QÆNNQ DEGRADACÆÃ@s)E; (NSEKSUALXNA REWOL@C)QÆQs)E; (NPROPAGANDA NASILXSTWAs